Effect injection of Ginger Extract on Development and Nucleus position of “Sangkuriang” Catfish Clarias sp. eggs - Junior, M. Zairin; Yustikasari, Y.; Arfah, H. (Jurnal Akuakultur Indonesia, 2005)
One of methods could be applied to continuously meet the need of fish fry including catfish (Clarias sp.) is artificial propagation by inducing ovulation and spawning.   As an alternative of existing method, in this study, ginger extract was intramuscularly injected to induce development of catfish eggs.  Ginger is known as an important regulator of the balance of arachidonat cycle.  The dose of ginger extract injected was 0, 0.5, 1.0 and 1.5 mL/kg broodstock.  The results of study showed that injection 100% of ginger extracts in all doses was insignificantly inducing development of egg diameter and its nucleus position of catfish.  Other chemicals exist in ginger extract might be functions as an obstacle for egg development of catfish. Keywords: catfish, Clarias sp., ginger, ovulation, egg   ABSTRAK Salah satu cara untuk memenuhi kebutuhan benih ikan termasuk lele (Clarias sp.) secara kontinyu adalah penggunaan teknologi pembiakan buatan melalui perangsangan ovulasi dan pemijahan. Sebagai alternatif teknik yang sudah ada, dicobakan perangsangan perkembangan telur ikan lele menggunakan bahan ekstrak jahe yang dilakukan melalui penyuntikan secara intramuskular. Jahe telah dikenal sebagai suatu pengatur penting atas keseimbangan siklus arakidonat. Dosis ekstrak jahe yang disuntikkan adalah 0, 0,5, 1 dan 1,5 mL/kg induk. Penyuntikan 100% ekstrak jahe pada semua dosis perlakuan belum dapat merangsang perkembangan diameter dan posisi inti sel telur ikan lele sangkuriang. Adanya bahan lain yang terdapat pada jahe diduga sebagai penghambat bagi perkembangan telur ikan lele. Kata kunci: Ikan lele, Clarias sp., jahe, ovulasi,  sel telur